HUBUNGAN MINAT BACA DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR EKONOMI SISWA KELAS XI IPS SMAN 10 PEKANBARU - Leni Marlina; Caska '; Mahdum ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2017)
The low learning motivation and interest in reading the economy so disappointinglearning outcomes of students, parents and teachers. It is characterized byinfrequent tasks done, enthusiasm in learning less and less active students in thelearning process. This study aims to examine the relationship between reading andlearning motivation and learning outcomes of economics. This study uses aquantitative approach. Data were collected using a questionnaire consisting of twoindependent variables, namely Reading Interest Economics (X1) and MotivationLearning Economic (X2) and one dependent variable is the Economic Study Results(Y). The whole population is used as a sample research (engineering samplesaturated). The number of students in class XI IPS SMAN 10 Pekanbarurespondent’s as many as 157 peoples. Prior research data was taken, first testedthe instrument to test the validity and reliability. Data were analyzed using the testfrequency, descriptive, product moment correlation. The results showed that there isa significant relationship between economic interests in reading the results of theeconomic study. Likewise, there is a significant relationship between motivations tolearn economics with the results of the economic study. There is a significantrelationship between economic interest in reading and motivation bilajar economytogether with the results of the economic study. The higher the reading and thestudents' motivation, the higher the economic learning outcomes achieved bystudents. Conversely the lower the interest in reading and learning motivation ofstudents it will also lower the learning results obtained by students.